Chemical and Photochemical Water Oxidation Mediated by an Efficient Single‐Site Ruthenium Catalyst. Issue 24 (14th December 2016) - Abdel‐Magied, Ahmed F.; Shatskiy, Andrey; Liao, Rong‐Zhen; Laine, Tanja M.; Arafa, Wael A. A.; Siegbahn, Per E. M.; Kärkäs, Markus D.; Åkermark, Björn; Johnston, Eric V.
Abstract: Water oxidation is a fundamental step in artificial photosynthesis for solar fuels production. In this study, we report a single‐site Ru‐based water oxidation catalyst, housing a dicarboxylate‐benzimidazole ligand, that mediates both chemical and light‐driven oxidation of water efficiently under neutral conditions. The importance of the incorporation of the negatively charged ligand framework is manifested in the low redox potentials of the developed complex, which allows water oxidation to be driven by the mild one‐electron oxidant [Ru(bpy)3 ] 3+ (bpy=2, 2'‐bipyridine). Furthermore, combined experimental and DFT studies provide insight into the mechanistic details of the catalytic cycle. Abstract : All the single sites ! A single‐site Ru water oxidation catalyst that houses a dicarboxylate‐based ligand is synthesized. The catalyst mediates the chemical and light‐driven oxidation of water efficiently under neutral conditions. Electrochemical studies and density functional calculations support the interesting redox features of the developed complex.